2000
DOI: 10.1016/s0022-5347(05)67020-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Urachal Cysts in Adulthood

Abstract: To minimize the morbidity of radical excision the laparoscopic management of benign urachal remnants in adulthood is efficacious and our preferred method of management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…We did not observe any symptom recurrence suggestive of incomplete excision during the follow-up period in our series, which agrees with most series of other reports using open traditional or robot-assisted techniques 9,10,19,22-27…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We did not observe any symptom recurrence suggestive of incomplete excision during the follow-up period in our series, which agrees with most series of other reports using open traditional or robot-assisted techniques 9,10,19,22-27…”
Section: Discussionsupporting
confidence: 91%
“…Since then, there have been several other case reports of laparoscopic excision of various types of urachal remnants in patients of various ages 15-18. There have also been two very short series of laparoscopic management of urachal remnants, one in four adults19 and one in four children 20. Both of these series used basically the same technique and showed that a laparoscopic technique can be used safely and effectively to remove all urachal remnant tissue with minimal morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…No patient developed local or distant recurrence at a mean follow-up of 6.5 months (range 4.5–9). Laparoscopic partial cystectomy has also been described for urachal cysts, vesical endometriosis, bladder pheochromocytoma, bladder leiomyoma, post-traumatic splenic pseudocyst, bladder schwannoma, and endometrioid adenocarcinoma [ 25 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…En caso de infección del quiste es recomendable realizar drenaje percutáneo del mismo junto con tratamiento antibiótico hasta control de la infección, para, en un segundo tiempo proceder a la extirpación quirúrgica 2,3,5,6 . En la actualidad el abordaje laparoscópico constituye la técnica quirúrgica de elección para el tratamiento del quiste de uraco 8, 10,15,16 .…”
Section: Figuraunclassified